2022 10th International Conference on Information and Education Technology (ICIET) 2022
DOI: 10.1109/iciet55102.2022.9778985
|View full text |Cite
|
Sign up to set email alerts
|

From Worklife Competencies to Educational Virtual Reality Implementations

Abstract: In this paper, we discuss how to implement educational virtual reality (VR) applications based on worklife competencies. VR is a technology increasingly used in education, and VR applications can be used, for example, in workplace learning and vocational education as well as in learning evaluation. We present a development workflow based on the good practices found and applied in multiple development cases. First, we describe the cases and use examples to illustrate competencies and their implementation in edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been shown that, with proper risk assessment, VRS development can also benefit from agile practices [97]. Agile development has been successfully used in various educational VRS tools and environments [98,99].…”
Section: Thematic Analysismentioning
confidence: 99%
“…It has been shown that, with proper risk assessment, VRS development can also benefit from agile practices [97]. Agile development has been successfully used in various educational VRS tools and environments [98,99].…”
Section: Thematic Analysismentioning
confidence: 99%